2020
DOI: 10.14238/pi60.6.2020.293-302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anaerobic gymnastics exercise on vascular endothelial growth factor in obese boys

Abstract: Background Vascular endothelial growth factor (VEGF) is the most important growth factor involved in angiogenesis and appears to be mediated through exercise training, leading to increased blood lactate. Objective To evaluate and compare the effects of anaerobic gymnastics exercise (AGE) on systemic VEGF in obese and normoweight boys.  Methods Sixty boys aged 8 to 12 years who enrolled in elementary level of gymnastics participated in this study and were randomly divided into four groups of 15 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The current meta-analysis of included studies showed inconsistent findings considering the effect of chronic physical activity on BDNF level. According to this, it was notified that BDNF level significantly increased [59,60,64,65,[67][68][69][70], decreased [61,62], and remained unchanged [63,66,71] after exercise intervention in patients with obesity. However, the lack of significant changes in BDNF levels following regular exercise in our meta-analysis could be due to the high heterogeneity in the studies included, which explains the inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…The current meta-analysis of included studies showed inconsistent findings considering the effect of chronic physical activity on BDNF level. According to this, it was notified that BDNF level significantly increased [59,60,64,65,[67][68][69][70], decreased [61,62], and remained unchanged [63,66,71] after exercise intervention in patients with obesity. However, the lack of significant changes in BDNF levels following regular exercise in our meta-analysis could be due to the high heterogeneity in the studies included, which explains the inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…The current meta-analysis of included studies showed inconsistent findings considering the effect of chronic physical activity on circulating BDNF level. According to this, it was notified that circulating BDNF level significantly increased [66,67,71,72,[74][75][76][77], decreased [68,69], and remained unchanged [70,73,78] after exercise intervention in patients with obesity. However, the lack of significant changes in circulating BDNF levels following regular exercise in our meta-analysis could be due to the high heterogeneity in the studies included, which explains the inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Human action recognition is a typical application based on statistical pattern recognition technology [19,20].…”
Section: Feature Extraction Methodmentioning
confidence: 99%